The Impact of Strengthening Character Education Based on Tri Hita Karana on Mathematics Learning Outcomes for Fourth-Grade Students - Putri, Made Diah Prabaswari; Suarjana, I Made; Yudiana, Kadek (Universitas Pendidikan Ganesha, 2023)
This research is motivated by students' low curiosity and behavior when learning mathematics. This is reflected in the unsatisfactory learning outcomes and the need for more motivation among students towards the subject. This study investigates and analyzes the strong influence of strengthening character education based on Tri Hita Karana on the significant improvement of mathematics learning outcomes of fourth-grade elementary school students. This research is an ex-post facto type, correlating the strengthening of character education based on Tri Hita Karana as the independent variable (X) and mathematics learning outcomes as the dependent variable (Y). The population of this study consists of 273 students, and the sample used in this research is 111 students obtained through cluster random sampling technique. Data collection is conducted using questionnaires and tests, and the data are analyzed using descriptive and inferential statistical analysis methods. The analysis process involves testing the prerequisite assumptions, including normality and linearity tests. Hypothesis testing is performed using simple regression analysis. The simple regression analysis results show a calculated value of r = 0.673, while the tabulated value at a significance level of 5% is 0.195. It indicates that the calculated value of r (0.673) is greater than the tabulated value (0.195), indicating a significant positive correlation between the strengthening of character education based on Tri Hita Karana and the mathematics learning outcomes of fourth-grade elementary school students. Therefore, it can be concluded that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.